Rectal gastrointestinal stromal tumor with early liver metastasis misdiagnosed as vaginal wall tumor: a rare case report - Yu, Xiuzhang; Fang, Zhijiang; Huang, Liyan; Qie, Mingrong; Xu, Xiumei; Yang, Bowen; Duan, Ruiqi (Frontiers in Oncology, 2025)
Rectal gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors of the gastrointestinal tract. They lack specific clinical manifestations and imaging characteristics, leading to a high risk of misdiagnosis and missed diagnosis. Here, we describe a 49-year-old female initially diagnosed with a vaginal wall tumor who underwent vaginal tumor resection surgery. The final diagnosis was a high-risk gastrointestinal stromal tumor (epithelioid type). Uniquely, one month after surgery, enhanced CT and PET/MR/CT scans indicated liver metastasis. The patient underwent a partial resection of the left liver and was subsequently treated with oral imatinib. Six months post-surgery, the patient has shown no signs of recurrence. This case accentuates the need for clinicians to improve their understanding of this disease to reduce the rates of misdiagnosis and missed diagnosis. Surgical resection is an effective treatment for localized rectal GISTs, but vigilance for distant metastasis is essential. Enhanced CT and PET/MR/CT scans are necessary. Female patients with GISTs located on the anterior rectal wall may be suitable for a vaginal approach surgery, however, the indications need further study. The importance of early differential diagnosis of rectal GISTs need to be highlighting.